Struktur Geologi dan Sebaran Batubara daerah Bentian Besar, Kabupaten Kutai Barat, Propinsi Kalimantan Timur - Widagdo, Asmoro (Jenderal Soedirman University, 2013)
This study is a surface geological mapping work to determine the geological conditions in the study area and in particular the presence of coal of Bentian Besar District, West Kutai Regency, East Kalimantan Province. The goal is to determine the position and spread of coal layer, coal quality and quantity of coal resources in the study area. Research on the existence of coal deposits is done through field survey methods, by observing, define and measure elements of geological structures encountered. At this stage of field work carried identification, observation, measurement of the coal position and takes it sample. In the study area encountered 2 (two) rock formations, Pamaluan, and Pulubalang Formation. Coal deposits found in rock unit known as Pulubalang Formation. Direction of the dip of the rock layers in the study area form a syncline structure. At this structure of the coal seam, there are three dip directions, namely: rocks on the southeast side of syncline axis tilted toward the northwest, rocks on the northwest side of the syncline axis tilted to the southeast, while the dip of the rocks on the southwest side Syncline tilted toward the northeast.